Gravity field recovery from geodetic altimeter missions. Issue 2 (15th July 2021) - Sandwell, David T.; Harper, Hugh; Tozer, Brook; Smith, Walter H.F.
Abstract: Satellite radar altimetry collected during a number of geodetic missions has provided a new understanding of the topography and tectonics of the deep oceans. As altimeter performance and coverage improves, smaller structures are revealed. Here we investigate the contribution of six altimeter missions that have been placed into geodetic mapping phases for more than one year. Two types of evaluations are performed. We first compare the composite (all six altimeters) grids of east and north vertical deflection to matching grids where one altimeter has been omitted evaluate their contribution versus latitude. We then estimate the noise in each altimeter by computing the median absolute deviation of the profiles with the best composite grid. Both analyses show that SARAL/AltiKa provides the greatest contribution and ERS-1 no longer provides any significant improvement. The major limitation for recovering small scale gravity features is the sea surface roughness from ocean waves. There have been steady improvements in instrumentation and processing methods that will continue into the future with higher frequency radars and interferometric swath altimeters planned for future missions.